Semi-analytic ray tracing method for time-efficient computing of transmission behavior of PCB level optical interconnects with varying core cross sections - Stübbe, Oliver (Optical Interconnects XVII)
Optical interconnects on printed circuit board level are a promising choice to support high bandwidth for short distance interconnects. These interconnects consists of highly multimode step index waveguides with rectangular core cross sections. Therefore ray tracing is an excellent method to determine the optical path parameters, e.g. optical power, ray path lengths and local ray directions. Based on these parameters the step response, the transient transfer function and the coupling behavior can be calculated. Classical ray tracing methods calculates the optical path parameters of each ray by successively computing internal reflections until a termination condition is reached. Therefore the computing time depends on the number of internal reflections. If the optical waveguide consists of cascaded straight and curved segments, e. g. point-to-point interconnects, one can use the analytic ray tracing method to determine the optical path parameters. The whole path parameters of each ray are determined by one analytical computation. The computing time depends on the number of segments. The analytic ray tracing method is unusable to determine ray path parameters of segments with varying core cross sections, e.g. tapers, crossings, splitters and combiners.